UPAYA INTERVENSI FISIK MELALUI SOSIALISASI SENAM OTAK (BRAIN GYM) SEBAGAI UPAYA MENGHAMBAT PROGRESIFITAS DAN MENURUNKAN ANGKA KEJADIAN DEMENSIA - Rivarti, Arina Windri; Saputri, Legis Ocktaviana; Harahap, Herpan Syafii; Nurhidayati, Nurhidayati; Suryani, Dini; Stephen, Mishael Enoch; Prawiro, Aurellia Wongso; Wulandari, Inayah; muttaqin, Syihabul; Ristia, Ovia Intan; Azizaturrahmah, Gina Aulia; Balqis, Ananda amirah (Universitas Mataram, 2024)
The high incidence of dementia not only poses health problems but also leads to significant social impacts and economic losses. While no potential therapy has been found to cure this disease, early diagnosis and prevention are important alternatives to prevent dementia. Brain gym is one of the physical activities known to enhance and maintain cognitive function. Various studies on brain gym have shown positive effects on the cognitive function of the elderly. This activity aims to provide socialization of Brain Gym to the community in Maringkik Island and is expected to have an impact on reducing the progression of cognitive impairment and dementia. This community service activity is divided into three stages, consisting of health education, health and cognitive function assessment, and socialization of brain gym movements to the community. This activity was enthusiastically attended by 50 participants from late adulthood to elderly. The activity went well until the end. Health education regarding brain gym techniques and benefits successfully introduced 9 types of brain gym movements and their benefits, which were well received and understood by the community. After the education session, the community successfully performed the brain gym movements introduced by the service team together. The socialization of brain gym to the community in Maringkik was carried out well with high enthusiasm from the community.